ANTI-INFLAMMATORY AND ANTI-HEMORRHOIDAL ACTIVITY OF POLYHERBAL GEL WITH THEIR CHARACTERIZATION USING CROTON OIL-INDUCED MODEL AND IN SILICO ACTIVITY AGAINST INFLAMMATORY MEDIATORS - AGGARWAL, ISHAN; UPADHYAY, SUKIRTI; KUMAR, ARVIND (International Journal of Applied Pharmaceutics, 2026)
ABSTRACT Objective: To formulate and optimize a polyherbal gel containing Azadirachta indica, Melia azedarach, Piper longum and Piper nigrum extracts and evaluate its anti-hemorrhoidal effect in rat model of croton oil-induced haemorrhoids and anti-diabetic effect by molecular docking. Methods: Using fruit extracts, HPLC and HPTLC analysis were used to analyse phyto-chemicals (azadirachtin, gallic acid, quercetin, rutin, ellagic acid, etc.). The gels were prepared using mixture of plant extract and optimized for anti-inflammatory activity. Evans blue extravasation, recto-anal coefficient, TNF-α, IL-6, neutrophil count and histopathological examination in wistar rats was done for anti-haemorrhoidal activity. In Silico activity of the bioactive compounds were attached to the inflammation and metabolism-related proteins, that is COX-2, 5-LOX, MMP-9 and α-glucosidase. Results: The extraction yield of A. indica fruits ranged from 1.6% to 4.8%, P. longum from 2.5% to 5.0%, P. nigrum from 2.1% to 4.4% and Melia azedarach was 5.1% in petroleum ether, 3.8% in chloroform, 3.4% in ethyl acetate and 5.3% in ethyl alcohol, with extraction times between 8 and 14 h. Among the solvents used, ethanol (95%) produced the highest extractive yield for all fruits. HPTLC of the combined mixture fraction showed peaks for rutin (Rf 0.16), gallic acid (Rf 0.47), quercetin (Rf 0.58), and ellagic acid (Rf 0.81), with additional peaks at Rf 0.34–0.38. Semi-quantitative analysis indicated rutin (2.8 mg/g), quercetin (2.5 mg/g), gallic acid (2.4 mg/g), and ellagic acid (1.3 mg/g). In the hemorrhoidal rat model, CMF (1:1:1:1) at 400 mg/kg reduced Evans blue to 0.38±0.02 µg/g, neutrophils to 16.5±0.6%, recto-anal coefficient to 0.91±0.01, serum TNF-α to 173.5±1.3 pg/ml, serum IL-6 to 91.2±0.6 pg/ml, protein TNF-α to 135.3±8.5 pg/mg, protein IL-6 to 248±12.0 pg/mg, and restored stool weight to 17.3±0.18 g. CMF (1:1:2:2) showed comparable reductions (Evans blue 0.37±0.02 µg/g; neutrophils 15.5±0.6%; recto-anal coefficient 0.89±0.01; serum TNF-α 166.8±1.2 pg/ml). Based on anti-hemorrhoidal activity CMF (1:1:1:1) and CMF (1:1:2:2) were selected for gel formulation. In the carrageenan-induced paw edema model, CMF-G1 (1111) reduced paw volume to 1.13±0.05 ml (2 h) and 0.95±0.04 ml (4 h), producing 48.2±0.31% edema inhibition, while CMF-G2 (1122) reduced paw volume to 1.20±0.02 ml (2 h) and 1.10±0.03 ml (4 h), with 35.4±0.42% inhibition, compared to 56.0±0.31% for diclofenac gel. Conclusion: The herbal gels formulated were effective and synergistic, exhibiting biphasic anti-hemorrhoidal and strong α-glucosidase inhibitory activities suggesting development of a novel treatment for hemorrhoids with simultaneous metabolic dysfunctions which is phytotherapeutic, safe and effective.